The Jews and the Mosaic law - Leeser, Isaac (Printed for the author, and sold by E. L. Carey and A. Hart, 1834)
pt. 1. A defence of the revelation of the Pentateuch, and of the Jews for their adherence to the same.--pt. 2. Four essays on the relative importance of Judaism and Christianity.